(untitled) (Fiep Bulletin - online, 2023)
In 2020, a new curricular reform was launched in Slovakia, which in the first phase is focused on primary and lower secondary education in primary school (Antala 2021; Masaryková 2021; Pupala and Fridrichová 2022). In our article, we want to indicate the direction in which the planned changes should go and how they will also affect the educational field of Health and Movement and the subject of physical and sports education: educational field Health and Movement and its focus, the main goals of the educational field, components of the educational field and tandem teaching of physical and sports education and its application in the lower primary school.